A CLINICO RADIOLOGICAL STUDY OF DISABILITIES AND DEFORMITIES OF HANSEN’S DISEASE IN A TERTIARY HEALTH CARE CENTRE - Dr. Balu Haridas; Dr. Krishna Talukdar; Dr. Rupak Bhuyan; Dr. Minakshi Narah; Dr. Pallabi Hatikakoty; Dr. Harmeet Singh. (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Hansen's disease remains a significant cause of preventable disability worldwide, with skeletal manifestations contributing substantially to patient morbidity. Despite advances in treatment, comprehensive documentation of clinical-radiological correlations in deformity patterns remains limited. This study aimed to evaluate the clinical features and radiological manifestations of disabilities and deformities in patients diagnosed with Hansen's disease.Methods: A cross-sectional observational study was conducted at the leprosy outpatient department of a tertiary healthcare institution. Forty-one patients with confirmed Hansen's disease presenting with deformities underwent comprehensive clinical examination, routine laboratory investigations, and specialized radiological assessment. Demographic characteristics, disease classification, occupational factors, and radiological findings were systematically documented and analysed.Results: Radiological bone changes were identified in 27 patients (65.85%), predominantly affecting males (77.78%, n=21) with a male-to-female ratio of 3.7:1. The majority of affected individuals were aged 26-55 years, with manual labourers comprising 29.63% of cases. Multibacillary leprosy demonstrated higher bone involvement, with lepromatous leprosy showing the highest prevalence (71.43%), followed by borderline lepromatous (70%) and pure neural subtypes (66.67%). Specific osseous changes included bone cysts (14.2%, n=4) and cortical thinning with irregularity (7.4%, n=3). Non-specific radiological manifestations encompassed soft tissue alterations (40.7%, n=13), distal phalangeal resorption (37%, n=10), subluxation (14.8%, n=4), and flexion deformities (11.3%, n=3).Conclusions: This investigation demonstrates significant radiological abnormalities in Hansen's disease patients with deformities, emphasizing the critical importance of early case detection and grade-1 disability recognition. The findings underscore the necessity for enhanced healthcare worker training in nerve function assessment and early intervention strategies to prevent progression from grade-1 to visible grade-2 disabilities, thereby reducing long-term morbidity and improving patient outcomes.